2019
DOI: 10.1111/ddi.12953
|View full text |Cite
|
Sign up to set email alerts
|

The role of cryptic diversity and its environmental correlates in global conservation status assessments: Insights from the threatened bird's‐eye primrose (Primula farinosa L.)

Abstract: Aim: Most of the fundamental questions in conservation biogeography require the description of species geographic boundaries and the identification of discrete biological units within these boundaries. International conservation efforts and institutions rely mainly on traditional taxonomic approaches for defining these boundaries, resulting in significant cryptic diversity going undetected and often extinct. Here, we combine high-throughput genomic data with publicly available environmental data to identify cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Southern-European bogs have a great naturalistic and biological value being relics of the Quaternary glaciations. Mires in southern Europe may be very old [389] and often harbor not only relict population of boreal species [390,391] but also endemics and specific genotypes of mire specialists [392,393]. Although disjunct occurrences and endemism of vascular plants in southern-European bogs are well known, less is known about smaller organisms such as diatoms.…”
Section: Mires (Peatlands): Fens and Bogsmentioning
confidence: 99%
“…Southern-European bogs have a great naturalistic and biological value being relics of the Quaternary glaciations. Mires in southern Europe may be very old [389] and often harbor not only relict population of boreal species [390,391] but also endemics and specific genotypes of mire specialists [392,393]. Although disjunct occurrences and endemism of vascular plants in southern-European bogs are well known, less is known about smaller organisms such as diatoms.…”
Section: Mires (Peatlands): Fens and Bogsmentioning
confidence: 99%
“…Therefore, it is an essential first step to identify the amount of cryptic species and genetic diversity, and then assess the role of environmental conditions that structure this diversity within a river catchment. This sets the framework for follow‐up studies that can investigate ecological preferences and trait variation arising from genetic variation (Bolnick et al., 2011; Theodoridis, Nogués‐Bravo, & Conti, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown several different alpine Primula species complexes to contain previously undescribed cryptic species, in China (Huang et al 2019; Ren et al 2020) and in Europe (Schorr et al 2013; Theodoridis et al 2019). Our findings on the P. cusickiana species complex resonate with these trends, and raise the question of what unique traits Primula possesses which might cause such frequent diversification via allopatric speciation.…”
Section: Discussionmentioning
confidence: 99%